Non-conventional operation modes for millimeter wave relativistic magnetrons - Gadetsky, N.P.; Lebedenko, A.N.; Magda, I.I.; Shtan’ko, A.A.; Volovenko, M.V. (Вопросы атомной науки и техники, 2016)
The operation of 8-mm band relativistic magnetrons is considered for traditional and inverted-voltage regimes.
The results obtained in a series of experiments are discussed. Работа посвящена исследованию релятивистских магнетронов 8-мм диапазона в традиционных и инвертированных режимах. Обсуждаются результаты, полученные в серии экспериментов. Робота присвячена дослідженню релятивістських магнетронів 8-мм діапазону в традиційному та інвертованому режимах. Обговорюються результати, отримані в серії експериментів.